Sichuan dark tea improves lipid metabolism and prevents aortic lipid deposition in diet-induced atherosclerosis model rats - Lu, Rui; Sugimoto, Takumi; Tsuboi, Tomoe; Sekikawa, Tatsushi; Tanaka, Mamoru; Lyu, Xiaohua; Yokoyama, Shinji (Frontiers in Nutrition, 2022)
Background and aims: Sichuan dark tea Zangcha (ST) is a traditional fermented Chinese tea found in Sichuan and Tibet and claimed for beneficial effects against lifestyle-related metabolic disorders. We examined the effects of ST on lipid metabolism and atherosclerosis. Methods and results: ST was given to fat-rich, diet-induced atherosclerosis model rats in comparison to dark-fermented Chinese Pu’erh tea (PT) and Japanese green tea (GT). After 8 weeks of feeding, ST and PT induced increase in high density lipoprotein (HDL)-cholesterol and decrease in glucose; ST decreased triglyceride in plasma. ST also induced low pH in cecum. There was no significant change in their body weight among the fat-feeding groups but a decrease was found in the visceral fat and liver weight in the ST group. Accordingly, ST reduced lipid deposition in the aorta in comparison to PT and GT. ST increased mRNA of LXRalpha, PPARalpha, PPARgamma and ABCA1 in the rat liver. The extract of ST stimulated the AMPK pathway to increase expression of ABCA1 in J774 cells and increased expression of lipoprotein lipase and hormone sensitive lipase in 3T3L1 cells, consistent with its anti-atherogenic effects in rats. High performance liquid chromatography analysis showed unique spectra of original specific compounds of caffeine and catechins in each tea extract, but none of them was likely responsible for these effects. Conclusion: ST increases plasma HDL and reduces plasma triglyceride to decrease atherosclerotic through AMPK activation. Further study is required to identify specific components for the effects in this tea preparation.